Measurement of aileron hinge moments and the effect of aileron trailing edge thickness - Schekman, Sjouke Willem (My University, 2016)
The objective of this research was twofold. The first objective was for the design and testing of a compact force measurement device, capable of fitting inside the wind tunnel model and measuring aileron hinge moments. Using the hinge moment balance, the second objective was to test the effect of varying the trailing edge thickness of the aileron. A plain type aileron, with a 20.6% chord and 40% span, was attached to a NACA 0012 wing. Four aileron test pieces with trailing edge thicknesses from 0.39%c to 1.22%c were used. A external balance capable of measuring the wing rolling and yawing moments was used in conjunction with the hinge moment balance. Validation of the results and performance of the hinge moment balance was done by comparisons to the data obtained from previous research and investigations using flow visualization. The results indicated that the system performed in a manner that was expected and predictable. The data from the hinge moment balance had an uncertainty of 4.2% which was deemed satisfactory for the purposes of this research. For the majority of the test cases the effects of the varied trailing edge thickness was found to be negligible. Small differences were noted at high angles of attack, above 15°, and high aileron deflections, above 20°. As these conditions were seen to be outside the typical flight envelope of general aviation aircraft, these small differences were seen as inconsequential. It was concluded that the use of an aileron with a thicker trailing edge would not have a negative effect on the performance of the aileron while allowing for less restrictions on the manufacture of the aileron itself.
A dissertation submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science in Engineering. Johannesburg, July-2015